2011
DOI: 10.1103/physreve.83.016207
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and chaos in the kicked top

Abstract: The standard kicked top involves a periodically kicked angular momentum. By considering this angular momentum as a collection of entangled spins, we compute the bipartite entanglement dynamics as a function of the dynamics of the classical counterpart. Our numerical results indicate that the entanglement of the quantum top depends on the specific details of the dynamics of the classical top rather than depending universally on the global properties of the classical regime. These results are grounded on linking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 35 publications
2
72
0
Order By: Relevance
“…Therefore, as discussed above and as Figs. 3(c) and 3(d) show, one needs to be careful with the initial states at the border [30] that has an average value of discord comparable to the value inside the chaotic sea. This is especially true for lower values of j such that the system is far from the classical limit.…”
Section: Dynamics Of Quantum Correlationsmentioning
confidence: 99%
“…Therefore, as discussed above and as Figs. 3(c) and 3(d) show, one needs to be careful with the initial states at the border [30] that has an average value of discord comparable to the value inside the chaotic sea. This is especially true for lower values of j such that the system is far from the classical limit.…”
Section: Dynamics Of Quantum Correlationsmentioning
confidence: 99%
“…I C incorporates insights similar to Ref. [9] about orbit delocalization but is significantly easier to compute. We see that I C correlates well with S Q across a wide range of system dynamical behaviors, and certainly does better than any attempt to correlate the entanglement with measures of chaos.…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively studied both theoretically and experimentally for over two decades [1][2][3][4][5][6][7][8][9] and continues to be investigated today [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these lines of research, there is an increased interest in the entanglement dynamics and its quantum-classical correspondence. Theoretically and experimentally it is observed that, there exist a clear relationship between quantum entanglement and classical chaos [Miller & Sarkar, 1999;Ghose & Sanders, 2004;Chaudhury et al, 2009;Lombardi & Matzkin, 2011;Lakshminarayan, 2001].…”
Section: Introductionmentioning
confidence: 99%